Perspektif Hukum Islam Dalam Pelaksanaan Nafkah Anak Setelah Perceraian Di Desa Nanga - Sari, Rahma Pramudya Nawang; Surabaya, Syarif Idris Pua; Kalsum, Umi; Natonis, Nurhayati; Sutantriyati, Ari (Universitas Cokroaminoto Yogyakarta, 2024)
In-depth examination of parents' post-divorce financial obligations is provided by this study, which takes into account the Compilation of Islamic Law in Nanga Mbaur Village, Sambi Rampas District, East Manggarai Regency. Researchers used a qualitative descriptive method that uses primary data sources that are directly gathered from informants via documentation and interviews. The study's findings suggest that parents should not assume they will always be able to provide for their children's needs when a divorce is decided. The imposition of child support following the divorce ruling was not carried out because of a number of reasons, including a deficiency of human resources, family dynamics, economic considerations, third-party considerations, and religious knowledge.